2021
DOI: 10.1097/bor.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

The association of Behçet's syndrome with HLA-B51 as understood in 2021

Abstract: Purpose of review To discuss clinical and pathogenic roles of HLA-B∗51 in Behçet's syndrome. Recent findings HLA-B∗51 remains the most important genetic factor in Behçet's syndrome, despite the recent identification of several susceptibility genes. The prevalence of HLA-B∗51 has been shown to differ among phenotype-based clinical clusters in the same patient population. HLA-B∗51 shows epistatic interaction with the susceptible allele of endoplasmic reticulum aminopeptidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Especially, in a Japanese cohort, the risk ratio was found to be 7.48 times higher in HLA-B51 carriers 13. Also, previous report showed that in various types, neuro-Beçhet’s disease have the highest rate of HLA-B51 positivity 14…”
Section: Discussionmentioning
confidence: 82%
“…Especially, in a Japanese cohort, the risk ratio was found to be 7.48 times higher in HLA-B51 carriers 13. Also, previous report showed that in various types, neuro-Beçhet’s disease have the highest rate of HLA-B51 positivity 14…”
Section: Discussionmentioning
confidence: 82%
“…Endoplasmic reticulum aminopeptidase 1 (ERAP1) may reflect common mechanisms with spondylarthritis by trimming the antigenic peptides to be loaded onto MHC class I molecules [ 21 ]. Although ERAP1 interacts with HLA-B51, it is not associated with vasculitis in BS [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been suggested that other features might be substituted for pathergy in these populations, including aseptic meningoencephalitis, cerebral vasculitis, recurrent phlebitis, arthritis, synovitis, epididymitis, or focal bowel ulceration [ 11 ]. HLA-B ∗ 51 remains the most important genetic factor in Behçet's disease, despite the recent identification of several susceptibility genes [ 12 ]. Some patients do not meet these criteria in whom the diagnosis of Behçet's disease is still made and establishing the diagnosis in such patients is much more difficult.…”
Section: Discussionmentioning
confidence: 99%